PERSEPSI MASYARAKAT DALAM PENGELOLAAN SAMPAH BERBASIS PARTISIPASI MASYARAKAT DI KOTA SURABAYA - Eri Witcahyo; Isa Ma'rufi (Fakultas Kesehatan Masyarakat, Universitas Jember, 2011)
By increasing human population, the problem of waste is become a serious problem in urban communities. Surabaya is the second largest city produce waste as much as 8,700 m3/day. Alternative solutions in dealing with municipal waste are waste management based on community’s participation. The purpose of this study was to determine the public perception in community-based waste management. Type of research is an observational by comparing between assisted and unassisted areas. Sample on research is 1000 people. Analyze technique used are descriptive and analytical. The results showed that respondents in assisted areas who have perception suggest in a way to handling municipal waste is sorting and processing at point of source (household/ neighborhood) are 72.6% (range 52.9 – 89.0%). The amount is higher than in the control/ unassisted areas, which only 43.9% respondents (34.8 – 76.2%) who have the same perception. Chi-square test result demonstrated the value of P = 0,000 which is smaller than α = 0.05. According to the result, it is suggested to assisting enhancement at communities by intensive and integrated surveillance monitoring supported. Establishment of natural leader from the communities is the effective’s way to optimizing the participation communities program. Keywords : perception, waste management, community’s participation